A nano-liposome formulation of the PARP inhibitor Talazoparib enhances treatment efficacy and modulates immune cell populations in mammary tumors of BRCA-deficient mice - Zhang, Di (Theranostics, 2019)
Two recently approved PARP inhibitors provide an important new therapeutic option for patients with BRCA-mutated metastatic breast cancer. PARP inhibitors significantly prolong progression-free survival in patients, but conventional oral delivery of PARP inhibitors is hindered by limited bioavailability and off-target toxicities, thus compromising the therapeutic benefits and quality of life for patients. Here, we developed a new delivery system, in which the PARP inhibitor Talazoparib is encapsulated in the bilayer of a nano-liposome, to overcome these limitations. Methods: Nano-Talazoparib (NanoTLZ) was characterized both in vitro and in vivo. The therapeutic efficacy and toxicity of Nano-Talazoparib (NanoTLZ) were evaluated in BRCA-deficient mice. The regulation of NanoTLZ on gene transcription and immunomodulation were further investigated in spontaneous BRCA-deficient tumors. Results: NanoTLZ significantly (p<0.05) prolonged the overall survival of BRCA-deficient mice compared to all of the other experimental groups, including saline control, empty nanoparticles, and free Talazoparib groups (oral and i.v.). Moreover, NanoTLZ was better tolerated than treatment with free Talazoparib, with no significant weight lost or alopecia as was observed with the free drug. After 5 doses, NanoTLZ altered the expression of over 140 genes and induced DNA damage, cell cycle arrest and inhibition of cell proliferation in the tumor. In addition, NanoTLZ favorably modulated immune cell populations in vivo and significantly (p<0.05) decreased the percentage of myeloid derived suppressor cells in both the tumor and spleen compared to control groups. Conclusions: Our results demonstrate that delivering nanoformulated Talazoparib not only enhances treatment efficacy but also reduces off-target toxicities in BRCA-deficient mice; the same potential is predicted for patients with BRCA-deficient breast cancer.